Synergistic hyperinflammation in IgA vasculitis complicated by varicella-induced HLH: a case report - He, Xiaoli; Zhou, Yu; Qiao, Lina; Li, Deyuan; Liu, Zhongqiang; Lu, Guoyan (Frontiers in Immunology, 2026)
Varicella-zoster virus (VZV)-induced hemophagocytic lymphohistiocytosis (HLH) is a rare but fatal complication, particularly in immunocompromised hosts. We present an 11-year-old boy with IgA vasculitis who developed severe VZV-HLH complicated by disseminated intravascular coagulation (DIC), acute liver failure and persistent lymphocytopenia. A multimodal therapeutic approach that combining high-dose acyclovir, intravenous immunoglobulin (IVIG), therapeutic plasma exchange (TPE), reduced-dose etoposide (75 mg/m²), and dexamethasone achieved rapid disease remission. This case demonstrates synergistic risk of HLH when VZV infection overlaps with IgA vasculitis, likely via compounded immune dysregulation. This case suggests that when varicella zoster virus infection overlaps with IgA vasculitis, it may synergistically increase the risk of HLH through aggravated immune dysregulation. In infection-triggered HLH, step-wise immunomodulatory therapy has a key role. What’s more, lymphocytopenia may be used as a biomarker to assess disease severity and recovery, and this finding emphasizes the need for long-term immune monitoring. This case provides valuable insights into the pathogenesis and management of VZV related HLH in rheumatic and immune diseases.